Open common bile duct exploration with primary closure treatment of complicated choledocholithiasis: a case report and literature review - Aldana, Edmundo H.; Mota, Eunice I.; Encinas, Jorge A.; Mijares, Diana L.; Aldana, Carlos H.; Ahumada, Leobardo; Alvarez, Luis A. (International Journal of Research in Medical Sciences, 2025)
Choledocholithiasis, a common complication of cholelithiasis, presents significant challenges in management, particularly in cases involving multiple or large stones. This case report describes a 55-year-old woman with multiple choledocholithiasis complicated by acute biliary pancreatitis, cholangitis, and cholecystitis. Initial management included endoscopic retrograde cholangiopancreatography (ERCP) with biliary stenting due to unsuccessful stone extraction, followed by open common bile duct (CBD) exploration with primary closure. The patient’s postoperative course was notable for a self-limiting grade A biliary leak, which resolved spontaneously. This case highlights the efficacy of primary closure in selected patients with a dilated CBD, despite the inherent risk of bile leakage, and underscores the importance of a multidisciplinary approach tailored to resource availability and surgical expertise. The findings in this case support primary closure as a viable option for complex choledocholithiasis, offering shorter hospital stays and reduced complications when performed in appropriate clinical settings.